Hubungan Kecemasan Dan Pengetahuan Dengan Kesiapan Menghadapi Persalinan Pada Ibu Hamil Trimester III - Nia Aprilia; Fathiyatur Rohmah (JURNAL RISET RUMPUN ILMU KESEHATAN, 2024)
Anxiety has a negative impact on pregnant women from conception to delivery by inhibiting growth and weakening uterine muscle contractions, among other things. Pregnant women who are anxious are more likely to have premature babies and even miscarriage. A lack of information and beliefs about what is valid (myths) can influence pregnant women's attitudes toward childbirth preparation, causing them to be unconcerned about childbirth preparation. This study aims to determine the relationship between anxiety and knowledge levels and childbirth preparedness in third trimester pregnant women at Kasihan II Primary Health Center. This research employed correlation analysis with cross sectional. The population in this study were third trimester pregnant women. In this study, there were 53 third trimester pregnant women at the Kasihan II Primary Health Center. Data collection techniques in this study used anxiety, knowledge and preparedness questionnaires. The data were then analyzed using the Spearman Rank Test. The study's findings revealed a 0.000 Sig (2-tiled) showing the relationship between the level of anxiety and childbirth preparedness at the Kasihan II Primary Health Center. The statistical test results showed Sig (2-tiled) 0.05, indicating that Ha is accepted, showing that there is a relationship between the level of anxiety and childbirth preparedness at the Kasihan II Primary Health Center. At the Kasihan II Primary Health Center, there is a Sig (2-tiled) value of 0.000 between Trimester III pregnant women's knowledge and their readiness for childbirth.  The statistical test results showed Sig (2-tiled) 0.05, indicating that Ha is accepted and that there is a relationship between third trimester pregnant women's knowledge and childbirth preparedness at the Kasihan II Primary Health Center. In order to reduce anxiety, it is hoped that third trimester pregnant women will learn as much about pregnancy as possible from the midwife during ANC. It is hoped that mothers will be able to attend classes for pregnant women held at the Puskesmas to further their education.